Health care access disparities across mainland Portugal: challenges to pursue the UN 2030 agenda for sustainable development - Vidal, Diogo Guedes (2020)
The UN 2030 Agenda for Sustainable Development defines the need to “ensure healthy lives and to promote wellbeing for all at all ages” as the Sustainable Development Goal 3 (SDG 3). This purpose is in alignment with the Portuguese National Health Service pillars that has established health care services as an universal service for all population. Despite there have been improvements on the national health care services, access to health care services continues to be an inequality issue in the Portuguese society. In the mainland, health services are clustered at the littoral while depopulated interior regions still suffer from lack of prompt specialized and adequate health services, especially in urgent situations. The present study, supported by data from two last census (2001 and 2011), focuses on how mortality is related to health services distribution – facilities and professionals – and how populations’ characteristics influence this situation. The results clearly exhibit a strong association between mortality and health services distribution, an association that is stronger in aged and illiterate populations. These results also suggest that public policies design should be reformulated according to the specificities and needs of each region population. This is a relevant issue to pursue the Sustainable Development Goals of the UN 2030 Agenda, namely to accomplish the SDG 10: “Reduce inequalities within and among countries”.